Molly's story - Cameron, W. Bruce; Cowdrey, Richard (New York : Starscape/A Tom Doherty Associates Book, 2017)
Molly's purpose is to take care of her girl, CJ, but CJ's mom will not allow her to have a dog, so Molly must stay hidden in CJ's room.
4.8
3-6
Keywords: Dogs -- Fiction; Human-animal relationships -- Fiction; Dogs -- Fiction; Human-animal relationship -- Fiction